The social responsibility of the housing sector and its role in achieving sustainable development: A sociological study on a sample of beneficiaries at the Mohammed bin Rashid Housing Establishment - in Dubai - Aljaaidi, Maryam; Al-Hourani, Mohammed (Al-Adab Journal, 2023)
This study aims to find out the relationship between the independent variables of the study and the degree of housing consideration for sustainable development in Dubai. To achieve the objectives of the study, a questionnaire was designed and applied to a random sample of 300 male and female beneficiaries of the housing of the Mohammed bin Rashid Housing Establishment. Descriptive and analytical statistics (frequencies, percentages, arithmetic mean, standard deviation and multiple regression coefficient) were used to know and analyze the demographic and social characteristics of the respondents, in which housing indicators for sustainable development in Dubai were learned. The results of the statistical analysis revealed the existence of an inverse and weak relationship between the variable number of housing members and the degree to which the housing takes into account sustainable development, (b*=-0.183, t=-2.074, p=0.040), while it was found that there was no relationship between the rest of the independent variables (the gender of the owner Dwelling, area name, type of dwelling, marital status, husband’s age, wife’s age, husband’s occupational status, wife’s occupational status, husband’s educational level, wife’s educational level, average monthly family income from all sources, duration of residence) and between the degree of observance of the housing in a way general.